2010
DOI: 10.1097/wnp.0b013e3181fe0709
|View full text |Cite
|
Sign up to set email alerts
|

Interictal Spikes Precede Ictal Discharges in an Organotypic Hippocampal Slice Culture Model of Epileptogenesis

Abstract: In organotypic hippocampal slice cultures, principal neurons form aberrant excitatory connections with other principal cells in response to slicing-induced deafferentation, similar to mechanisms underlying epileptogenesis in post-traumatic epilepsy. To investigate the consequences of this synaptogenesis, we recorded field potential activity from area CA3 during perfusion with the complete growth medium used during incubation. At 7 days in vitro (DIV), slice cultures only displayed multi-unit activity. At 14 DI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
110
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 36 publications
10
110
0
Order By: Relevance
“…Early epileptiform activity in electrographic recordings is a promising predictor of epilepsy after brain injury induced by kainic acid . Similar results were obtained in vitro in the organotypic hippocampal slice culture model of epileptogenesis (Dyhrfjeld-Johnsen et al 2010). These studies undertook a simple but important step beyond prior EEG biomarker studies by greatly increasing the duration of the EEG sample from the standard clinical EEG of tens of minutes up to 24-h recording epochs (Jennett and Van De Sande 1975).…”
Section: Electrographic Biomarkerssupporting
confidence: 57%
“…Early epileptiform activity in electrographic recordings is a promising predictor of epilepsy after brain injury induced by kainic acid . Similar results were obtained in vitro in the organotypic hippocampal slice culture model of epileptogenesis (Dyhrfjeld-Johnsen et al 2010). These studies undertook a simple but important step beyond prior EEG biomarker studies by greatly increasing the duration of the EEG sample from the standard clinical EEG of tens of minutes up to 24-h recording epochs (Jennett and Van De Sande 1975).…”
Section: Electrographic Biomarkerssupporting
confidence: 57%
“…The pH was adjusted to be between 7.35 and 7.40 using NaOH. Previous studies have shown that hippocampal organotypic slices can be used as a post-traumatic model of epileptogenesis (Dyhrfjeld-Johnsen et al, 2010;Berdichevsky et al, 2012). By 7 d in vitro the tissue has recovered from the acute trauma associated with the slicing process and the neurons exhibit hyperexcitability, probably due to increased connectivity (Berdichevsky et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The use of organotypic hippocampal cultures, where epileptogenesis occurs on a compressed time scale,23, 24 and where seizures and seizure‐induced cell death can be easily quantified with biomarker assays,30, 31 allowed us to circumvent the throughput limitations of in vivo chronic epilepsy models 4. Thus, we were able to screen 140 compounds and combinations of compounds, in over 400 separate drug‐concentration experiments, and identify over 40 hits.…”
Section: Discussionmentioning
confidence: 99%
“…In light of this abundant reciprocal excitation, it is not surprising that organotypic slice cultures are hyperexcitable19 and even spontaneously epileptic20, 21 (see Heinemann and Staley22 for review). We have characterized epileptogenesis in this preparation 23, 24. Increases in extracellular lactate accompanied seizures in human hippocampus,25, 26 and we found that lactate production was correlated with seizure‐like activity in organotypic cultures.…”
Section: Introductionmentioning
confidence: 91%